Pradhan Mantri Ujjwala Yojana: A Meaningful Step Towards Women's Health and Environmental Awareness: प्रधानमंत्री उज्ज्वला योजना: महिलाओं के स्वास्थ्य और पर्यावरण चेतना की दिशा में एक सार्थक कदम - Sharma, Anjubala (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The objective of the Pradhan Mantri Ujjwala Yojana (PMUY) is to provide clean and safe cooking fuel to poor families, particularly women living in rural areas. This scheme is an effective effort to reduce the smoke and health problems associated with the use of traditional fuels. This research article analyzes the scheme's positive impact on health and its role in promoting environmental awareness. The study found that the use of Liquefied Petroleum Gas (LPG) under the scheme has led to an improvement in women's health and a change in their living standards. Additionally, it represents an important initiative towards environmental protection, as it has proven helpful in reducing air pollution. Abstract in Hindi Language: प्रधानमंत्री उज्ज्वला योजना (PMUY) का उद्देश्य गरीब परिवारों, विशेष रूप से ग्रामीण क्षेत्रों में रहने वाली महिलाओं को स्वच्छ और सुरक्षित खाना पकाने के ईंधन की सुविधा प्रदान करना है। यह योजना पारंपरिक ईंधनों के उपयोग से होने वाले धुएं और स्वास्थ्य संबंधी समस्याओं को कम करने के लिए एक प्रभावी प्रयास है। इस शोध लेख में योजना के स्वास्थ्य पर सकारात्मक प्रभाव और पर्यावरण चेतना को बढ़ावा देने में इसकी भूमिका का विश्लेषण किया गया है। अध्ययन में पाया गया कि योजना के तहत रसोई गैस (LPG) के उपयोग से महिलाओं के स्वास्थ्य में सुधार हुआ है और उनके जीवन स्तर में भी बदलाव आया है। इसके साथ ही, यह पर्यावरण संरक्षण की दिशा में भी एक महत्वपूर्ण पहल है, क्योंकि यह वायु प्रदूषण को कम करने में मददगार साबित हुई है। Keywords: प्रधानमंत्री उज्ज्वला योजना, महिलाओं का स्वास्थ्य, पर्यावरण चेतना, स्वच्छ ईंधन